A comparison between veterinary small animal general practitioners and emergency practitioners in Australia. Part 1: demographic and work-related factors - Li, Kun; Mooney, Erin; McArthur, Michelle; Hall, Evelyn; Quain, Anne (Frontiers in Veterinary Science, 2024)
Occupational stressors are commonly encountered in small animal veterinary practice and have been associated with burnout. The working context of veterinarians differs by specialty, and this can potentially lead to variable exposures to risk factors for burnout. The aim of this study was to explore differences in demographic and working conditions of veterinary general practitioners (GPs) and emergency practitioners (EPs) to compare exposure to different potential stressors. An anonymous, online survey was administered to veterinary GPs and EPs practicing in metropolitan regions of Australia. In total, 320 participant responses were analyzed (n = 237, 74.2% GPs and n = 83, 25.9% EPs). Significant differences (P < 0.05) in the demographics and work-related exposures were found between the two groups. GPs were found to be older than EPs with a greater number of years of experience in their field (P < 0.001). Most veterinary GPs worked only day shifts (207/236, 87.7%); where EPs worked a greater variety of shift patterns, with “only day shifts” being the least common shift pattern (P < 0.001). Most GPs worked a set and predictable roster pattern (195/236, 83.6%), while most EPs did not (51/83, 61.5%). EPs worked more weekends and public holidays (P < 0.001). The EP group performed more hours of work each week but worked less overtime. The main contributing factors for overtime were scheduling factors for GPs and staffing issues for EPs. EPs were commonly not able to take meal-breaks and GPs' meal-breaks were commonly interrupted by work. EPs were more frequently exposed to patient death, euthanasia (including for financial reasons), emotionally distressed clients and delivering negative news (P < 0.001). Both groups indicated that most work environments were collegiate and supportive, and a minority reported toxic colleagues (11.8%) or management teams (26.9%). Just under one-half of respondents reported having witnessed or experienced workplace bullying. Of our respondent group, 52.0% (166/319) were not satisfied with their remuneration. Desire to leave their principal area of practice was prevalent among this survey group (192/319, 60.2%) with approximately one-third considering leaving the veterinary profession. We discuss the implications of these workplace factors, including mitigation strategies.